The Influence of the Insertion Angle on Middle and Lower Face Tissue-Mechanics When Treating the Nasolabial Folds with Facial Suspension Threads—An Experimental Split-Face Cadaveric Study - Braun, Martin; Frank, Konstantin; Freytag, David L.; Gotkin, Robert H.; Lachman, Nirusha; Hsu, Gloria; Gavril, Diana L.; Silva, Maria V.; Bialowas, Christie; Cotofana, Sebastian (Facial Plastic Surgery, 2020)
A novel treatment approach to address the nasolabial fold is the insertion facial suspension threads. However, there is a paucity of data available to guide insertion techniques and material selection. Three female and two male cephalic specimens of Caucasian ethnicity (73.6 ± 6.5 years; 21.41 ± 2.2 kg/m2) were included into this experimental split-face study. One facial side was treated with polycaprolactone (PCL) thread: 180 mm, bidirectional, 18G 100 mm cannula, 20 degrees trajectory, preauricular approach whereas the contralateral side was treated with polydioxanone (PDO) thread: 100 mm, bidirectional, 19G, 60 mm cannula, 50 degrees trajectory, infraorbital approach. Three-dimensional imaging outcome measures included vertical and horizontal skin displacement and volume changes at the nasolabial sulcus, at the labiomandibular sulcus, and along the jawline. Comparing PCL 180 mm 20 degrees to PDO 100 mm 50 degrees: vertical lifting effect 1.42 ± 2.63 mm versus 1.24 ± 1.88 mm (p = 0.906); horizontal lifting effect 3.42 ± 1.44 mm versus –2.02 ± 1.84 mm (p = 0.001); nasolabial volume change –0.80 ± 0.65 mL versus –0.52 ± 0.17 mL (p = 0.367); labiomandibular volume change –0.45 ± 0.42 mL versus –0.16 ± 0.16 mL (p = 0.191); jawline volume change 0.02 ± 0.43 mL versus –0.01 ± 0.21 mL (p = 0.892). The study provides objective evidence for the short-term effectiveness of facial suspension threads in treating the nasolabial folds. The results point toward a better aesthetic outcome when utilizing long facial suspension threads that can effect full-face changes as compared with short facial suspension threads.
Keywords: facial suspension threads; face; anatomy; soft tissue repositioning